2017
DOI: 10.1073/pnas.1701703114
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin and LGN align epithelial cell divisions with tissue tension independently of cell shape

Abstract: Tissue morphogenesis requires the coordinated regulation of cellular behavior, which includes the orientation of cell division that defines the position of daughter cells in the tissue. Cell division orientation is instructed by biochemical and mechanical signals from the local tissue environment, but how those signals control mitotic spindle orientation is not fully understood. Here, we tested how mechanical tension across an epithelial monolayer is sensed to orient cell divisions. Tension across Madin-Darby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 60 publications
(93 reference statements)
12
104
3
Order By: Relevance
“…Contrary to observations in monolayers (Hart et al, 2017), we found that cells in stretched tissue divide according to cell shape both when θ J is oriented with (Figure 3A) and against (Figure 3B&C) the direction of stretch. Moreover, in the case of cells that are relatively round in shape (C J >0.65), there is no preference for aligning with the global stretch direction and indeed alignment with TCJ shape still appears more accurate than with the stretch axis (Figure S2A&B; p < 0.005 for TCJS, not significant for stretch direction, Mann-Whitney U test).…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to observations in monolayers (Hart et al, 2017), we found that cells in stretched tissue divide according to cell shape both when θ J is oriented with (Figure 3A) and against (Figure 3B&C) the direction of stretch. Moreover, in the case of cells that are relatively round in shape (C J >0.65), there is no preference for aligning with the global stretch direction and indeed alignment with TCJ shape still appears more accurate than with the stretch axis (Figure S2A&B; p < 0.005 for TCJS, not significant for stretch direction, Mann-Whitney U test).…”
Section: Resultscontrasting
confidence: 99%
“…Previous studies have shown that cell division in epithelia can increase in rate and acquire a directional bias following an externally imposed anisotropic mechanical strain, similar to what we see in host cells neighbouring a kRas V12 cluster [34,36,[92][93][94]. By analysing the orientation of a cell's long axis, we found that wild-type cells close to GFP-kRas V12 cell clusters demonstrated features consistent with the presence of anisotropic stress [95], that were absent in wild-type cells close to cMYC expressing clusters [35,[62][63][64][65].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, our experiments tested the effects of acute application of tensile stress. Other mechanisms can be elicited when stresses are applied more slowly or sustained longer, such as cellular rearrangements and oriented cell division (Hart, et al, 2017;Etournay, et al, 2015;Wyatt, et al, 2015;Campinho, et al, 2013). Lessey, E.C., Guilluy, C., and Burridge, K. (2012).…”
Section: Discussionmentioning
confidence: 99%